Biological chemistry. Section 1. Сommon regularities of metabolism and energy exchange. Metabolism of carbohydrates, lipids and amino acids and its regulation : handbook for independent work at home and in class preparation for component of USQE ‘KROK-1, Dentistry’ for students specialty 221 "Dentistry" - Shwets, V. M.; Ivanchenko, D. H.; Mykhalchenko, Ye. K.; Швець, Володимир Миколайович; Іванченко, Дмитро Григорович; Михальченко, Євген Костянтинович (Запорізький державний медико-фармацевтичний університет, 2025)
This manual is recommended to use for students of III International faculty the second year of study for independent work in Biochemistry discipline at home and in class.